Survival and Axonal Outgrowth of the Mauthner Cell Following Spinal Cord Crush Does Not Drive Post-injury Startle Responses - Zottoli, Steven J.; Faber, Donald S.; Hering, John; Dannhauer, Ann C.; Northen, Susan (Frontiers in Cell and Developmental Biology, 2021)
A pair of Mauthner cells (M-cells) can be found in the hindbrain of most teleost fishes, as well as amphibians and lamprey. The axons of these reticulospinal neurons cross the midline and synapse on interneurons and motoneurons as they descend the length of the spinal cord. The M-cell initiates fast startle responses (fast C-starts) in goldfish and zebrafish triggered by abrupt acoustic/vibratory stimuli. Starting about 70 d after whole spinal cord crush, less robust startle responses with longer latencies are manifest in adult goldfish, Carassius auratus. The morphological and electrophysiological identifiability of the M-cell provides a unique opportunity to study cellular responses to spinal cord injury and the relation of axonal regrowth to a defined behavior. After spinal cord crush at the spinomedullary junction about 1/3rd of the damaged M-axons of adult goldfish send at least one sprout past the wound site between 56-85 d postoperatively. These caudally projecting sprouts follow a more lateral trajectory relative to their position in the fasciculus longitudinalis medialis of control fish. Other sprouts, some from the same axon, follow aberrant pathways that include rostral projections, reversal of direction, midline crossings, neuromas and projection out the first ventral root. Stimulating M-axons in goldfish that had recovered startle behavior between 198-468 d postoperatively resulted in no or minimal EMG activity in trunk and tail musculature as compared to control fish. Although M-cells can survive for at least 468 d after spinal cord crush, maintain regrowth, and elicit putative trunk EMG responses, the cell does not appear to play a substantive role in the emergence of acoustic/vibratory triggered responses. We speculate that aberrant pathway choice of this neuron may limit its role in the recovery of behavior and discuss structural and functional properties of alternative candidate neurons that may render them more supportive of post-injury startle behavior.